The impact of responsible leadership on knowledge sharing behavior through the mediating role of person−organization fit and moderating role of higher educational institute culture - Haider, S. A.*; Akbar, Ahsan; Tehseen, Shehnaz *; Jaleel, Farrokh (Elsevier, 2022)
The aim of this study is to investigate the effect of responsible leadership on knowledge sharing behavior. Furthermore, we investigated the mediating role of person-organization fit in the relationship between responsible leadership and knowledge sharing behavior. Moreover, higher educational institute culture moderates the relationship between responsible leadership and person-organization fit. The data collected from 295 respondents (teachers, head of department and management staff) from universities located in different cities of China. The data were gathered at one time, and therefore, the study is cross-sectional. Because of COVID-19, there have been a few universities closed; therefore, data were also collected online. The data were analyzed quantitatively using the partial least squares (PLS)−structural equation modelling (SEM) technique. The result indicated that responsible leadership is positively and significantly influential on knowledge sharing behavior directly, and also indirectly through mediator person-organization fit. Also, the higher educational institute culture positively and significantly moderates the relationship between responsible leadership and person-organization fit.